The Safety of Foot and Ankle Surgical Procedures at an Ambulatory Surgery Center. Issue 4 (22nd October 2020) - Peters, Wesley D.; Adamson, Peter J.; Janney, Cory; Panchbhavi, Vinod K.
Category: Ankle; Bunion; Hindfoot; Lesser Toes; Midfoot/Forefoot Introduction/Purpose: There is a growing trend to perform surgical procedures at freestanding ambulatory surgical centers. No literature exists evaluating the rate of adverse events and overall safety of foot and ankle outpatient surgeries at a freestanding ambulatory surgery center (ASC). Methods: A retrospective review of all foot and ankle cases performed over a two year period at a single freestanding ASC. A total of 313 cases were performed. Adverse events are state-reported events that cause harm or lead to additional treatment. Using state-reported adverse events criteria and previous literature from hand and upper-extremity cases, we categorized our adverse events into seven categories: 1) infection requiring intravenous abx or return to the operating room, 2) postoperative transfer to a hospital, 3) wrong-site surgery, 4) retention of a foreign object, 5) postoperative symptomatic thromboembolism (DVT), 6) medication error, and 7) bleeding complications. Results: The overall rate of adverse events was 3.5% with 11 events identified over the two year period. There were a total of 10 infections and 1 symptomatic DVT. There were no cases that resulted in transfer to a hospital, hospital admission after discharge, medication error, bleeding complications, wrong-site procedures, or retained foreign bodies. Conclusion: Outpatient foot and ankle procedures are not without complications, but the overall rate of complications postoperatively is farly low (3.5%). Overall, foot and ankle surgeries can be performed safely in an outpatient setting at an ASC.